The Transfer of Asylum Seekers in Australia to Third Countries: A Case Study of Sovereignty versus International Law - Tuckfield, Hugh S. (Kathmandu School of Law Review, 2013)
Asylum is an issue equally central to refugee law and human rights. Generally, they are protected under the 1951 Refugee Convention, but asylum cases are largely state regulated affair, subject to state legislations, policies and guidelines, which certainly do not preclude the applicability of international obligations directing the conduct of state towards the asylum seekers, which emanate from the recognized international human rights principles such as right to seek asylum and right against refoulement and right not to be arbitrarily detained. Contracting parties to international conventions such as the 1951 Refugee Convention, ICCPR, ISESCR, CAT, CRC, CEDAW and CERD among others acquire the responsibility to respect, protect and fulfill the obligations adducible in treatment of asylum seekers. In this regard, Australia was one of the earliest state parties to the 1951 Refugee Convention and is also a party to the relevant human rights treaties. However, it is determined to adhere to its conventional understanding of sovereignty and nationalism, at the cost of comprising the minimum protection of the rights of those who seek asylum in it.